Free will: A very short introduction - Pink, Thomas (Oxford Oxford university press, 2004)
Every day we seem to make and act upon all kinds of choices: some trivial, others so consequential that they change the course of one's life, or even the course of history. But are these choices really free, or are we compelled to act the way we do by factors beyond our control? Is the feeling that we could have made different decisions just an illusion? And if our choices are not free, is it legitimate to hold people morally responsible for their actions?Thomas Pink looks at the fundamental philosophical question of free will, critically examining the claim: If our actions are causally determined by events beyond our control, that means that we can never act freely, and so can never be held responsible for our actions.